2016
DOI: 10.1002/cpp.2024
|View full text |Cite
|
Sign up to set email alerts
|

The Inference‐Based Approach (IBA) to the Treatment of Obsessive–Compulsive Disorder: An Open Trial Across Symptom Subtypes and Treatment‐Resistant Cases

Abstract: Psychological treatment based on the inference-based approach is an effective treatment for all major subtypes of obsessive-compulsive disorder. The treatment is equally effective for those with high and low levels of overvalued ideation. Treatment based on the inference-based approach may be particularly valuable for those who have shown an attenuated response to cognitive-behaviour therapy as usual.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 80 publications
2
15
0
Order By: Relevance
“…To our knowledge, the current study is the only study to have used both a longitudinal design and hierarchical multiple regression analyses to explore whether treatment‐related improvements in OCD beliefs would predict improvements in specific OCD symptom dimensions (independent of improvements in depressive symptoms). This extends on previous research by Aardema, O'Connor, Delorme, and Audet () who reported that participants receiving treatment for OCD demonstrated treatment‐related improvement on all OCD belief domains regardless of their primary OCD concern. In the current study, improvements in beliefs about the importance and control of thoughts significantly predicted improvements in repugnant obsessions, a finding largely consistent with cross‐sectional data.…”
Section: Discussionsupporting
confidence: 86%
“…To our knowledge, the current study is the only study to have used both a longitudinal design and hierarchical multiple regression analyses to explore whether treatment‐related improvements in OCD beliefs would predict improvements in specific OCD symptom dimensions (independent of improvements in depressive symptoms). This extends on previous research by Aardema, O'Connor, Delorme, and Audet () who reported that participants receiving treatment for OCD demonstrated treatment‐related improvement on all OCD belief domains regardless of their primary OCD concern. In the current study, improvements in beliefs about the importance and control of thoughts significantly predicted improvements in repugnant obsessions, a finding largely consistent with cross‐sectional data.…”
Section: Discussionsupporting
confidence: 86%
“…This measure was designed specifically for the study and was inspired by the postulate of cognitive theory according to which change in cognition brings change in emotions and behaviors ( 8 ). Many other studies have used this methodology ( 24 , 25 ) and this type of measure has been previously validated ( 26 ). The idiosyncratic measure asks participants to name the thoughts that would be targeted by APAP and to rate the degree of conviction in each thought in percentage.…”
Section: Methodsmentioning
confidence: 99%
“…Inference‐based therapy is designed to ameliorate doxastic obsessions by identifying bad inferences that produce or sustain these obsessions (Clark & O'Connor, , p. 152–153). Practitioners help patients resist these inferences by redirecting the patient's attention to more relevant evidence, drawing out the differences between inferences made in obsessive and nonobsessive contexts, and replacing obsessive narratives with more plausible nonobsessive narratives (Clark & O'Connor, , p. 165–169; Julien et al, , p. 189–190; Aardema et al, ).…”
Section: Ct As An Antidote To Level Splittingmentioning
confidence: 99%
“…Traditional CTs are remarkably effective (McKay et al, ), and emerging treatments such as inference‐based therapy are promising (Aardema et al, ). In what follows, I offer a philosophical account that helps explain why these CTs work as well as they do.…”
Section: Ct As An Antidote To Level Splittingmentioning
confidence: 99%
See 1 more Smart Citation